FEATURES OF CORONARY ATHEROSCLEROSIS IN PATIENTS WITH COMBINATION STABLE ANGINA AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - V. K. Zafiraki; K. V. Skaletckii; T. V. Stavenchuk; N. A. Maltabar; E. D. Kosmachova (Кубанский научный медицинский вестник)
Features of coronary atherosclerosis were estimated in patients with a combination of stable angina and chronic obstructive pulmonary disease (COPD) who underwent coronary artery bypass graft surgery (CABG). More severe coronary lesions in group with combination of coronary artery disease (CAD) and COPD were revealed. Number of hemodynamically significant stenoses weakly correlated with the severity of COPD. In patients with combination CAD and COPD total number of stenoses and the number of hemodynamically significant stenoses was higher than in the control group. As well extended stenoses were more common in patients with COPD. At the same time, there were no differences in the number of critical stenoses and occlusions between groups.